Factors Affecting Females’ Occupational Aspirations: A Synthesis of the Literature - Dr. Andleeb (Voices of Teachers and Teacher Educators, 2020)
The concept of occupational aspiration appears within career developmental theories as an important milestone in adolescents’ career developmental; required for seeking careers that are compatible with their self-concepts. Many researches consider occupational aspiration as significant career motivational variable that is capable of predicting levels of future career attainment. Many studies suggest that gender is a significant factor in predicting students’ levels of occupational aspiration. Gender is clearly one of the most powerful of all influences on vocational behavior (Osipow & Fitzgerald, 1996). This paper is an attempt to synthesize career literature that shows females’ occupational aspirations are lower than their male counterparts. Withthe synthesis of literature, this study attempts to find out those factors that are responsible for lower occupational aspirations of females. The lower occupational aspirations of females may be explained in terms of understanding factors that influence occupational aspirations - factors such as gender, race, socio-economic status, parents’ occupation, their educational level, and parental expectations. The study further suggests what measure could be taken to enhance females’ occupational aspirations